Flexural strength of acrylic resin repairs processed by different methods: water bath, microwave energy and chemical polymerization - João Neudenir Arioli Filho; Luís Eduardo Butignon; Rodrigo de Paula Pereira; Matheus Guilherme Lucas; Francisco de Assis Mollo Junior (University of São Paulo, 2011)
Denture fractures are common in daily practice, causing inconvenience to the patient and to the dentists. Denture repairs should have adequate strength, dimensional stability and color match, and should be easily and quickly performed as well as relatively inexpensive. OBJECTIVE: The aim of this study was to evaluate the flexural strength of acrylic resin repairs processed by different methods: warm water-bath, microwave energy, and chemical polymerization. MATERIAL AND METHODS: Sixty rectangular specimens (31x10x2.5 mm) were made with warm water-bath acrylic resin (Lucitone 550) and grouped (15 specimens per group) according to the resin type used to make repair procedure: 1) specimens of warm water-bath resin (Lucitone 550) without repair (control group); 2) specimens of warm water-bath resin repaired with warm water-bath; 3) specimens of warm water-bath resin repaired with microwave resin (Acron MC); 4) specimens of warm water-bath resin repaired with autopolymerized acrylic resin (Simplex). Flexural strength was measured with the three-point bending in a universal testing machine (MTS 810 Material Test System) with load cell of 100 kgf under constant speed of 5 mm/min. Data were analyzed statistically by Kruskal-Wallis test (p<0.05). RESULTS: The control group showed the best result (156.04±1.82 MPa). Significant differences were found among repaired specimens and the results were decreasing as follows: group 3 (43.02±2.25 MPa), group 2 (36.21±1.20 MPa) and group 4 (6.74±0.85 MPa). CONCLUSION: All repaired specimens demonstrated lower flexural strength than the control group. Repairs with autopolymerized acrylic resin showed the lowest flexural strength.